Truth as a case of practice. Remarks on the periphery of the dogmatic concept of objective truth - Jaśkiewicz, Jacek (Acta Universitatis Lodziensis. Folia Iuridica, 2014)
The article has been thought as a contribution to the discussion on comprehension of truth within the framework of the domestic jurisprudence. The author, describing philosophical and theoretical assumptions with respect to positivism epistemology indicates - basing on the sources presented in this article - the transformations to which the concept of the so-called ‘objective truth’ was subject and the extent to which various political and social factors influenced the concept mentioned. As he concludes complexity and dynamics concerning transformations of the domestic legal culture, as well as conflicts between the written law and the practice are disclosed in lawyers’ attitude to the truth.